Pengaruh Semangat Kerja Terhadap Kinerja Karyawan PT “PPA” Cabang Pekanbaru - Ansori, Putra Budi; Salina, Nur (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This study aims to analyze the influence of work spirit on employee performance at PT "PPA" Pekanbaru Branch. The research employs a quantitative approach using observation and questionnaire data collection techniques. The population and sample consist of 32 employees. Data were analyzed using simple linear regression with SPSS version 25. Validity tests show all statement items are valid (r count > 0.349) and reliable (Cronbach's Alpha > 0.6). The Kolmogorov-Smirnov normality test indicates normally distributed data (sig. 0.200 > 0.05). Regression analysis yields the equation Y = 28.129 + 1.310X + e, with t count (6.663) > t table (2.042) and significance 0.000 < 0.05. The coefficient of determination shows work spirit influences employee performance by 59.7%, while 40.3% is influenced by other variables. The conclusion is that work spirit significantly affects employee performance at PT "PPA" Pekanbaru Branch. Higher employee work spirit correlates with increased performance. Keywords: work spirit, employee performance